PRÁTICAS TRADUTÓRIAS NA ESPANHA: O TRABALHO DO TRADUTOR E SUAS FRONTEIRAS - Francisco, Amanda Ramos (Organon, 2004)
This article intends to propose some of the main features that interfere with the translators’ work. Someof these restrictions are the status of the source text, as well as that of the source and the target literatures. Anotherimportant factor that must be considered when studying translated texts is the patronage involved, that is, the goalsof each translation must be taken into account. Similarly, the values of the receptor culture, which usually are alsothe translator’s values, are important tools for the assessment of translation products. This article brings examplesof different translation practices in Spain, such as that of the Church translators in the XII century, and that of theKing translators in the 1200’s, as well as those developed in the XVIII/XIX centuries. These periods are allconsidered by many scholars to be times of intense production of translations.